Serotype Distribution, Antimicrobial Resistance, and Class 1 Integrons Profiles of Salmonella from Animals in Slaughterhouses in Shandong Province, China - Zhao, Xiaonan; Ye, Chaoqun; Chang, Weishan; Sun, Shuhong (Frontiers in Microbiology, 2017)
The current study aimed to analyze the prevalence and characterization of Salmonella enterica isolated from animals in slaughterhouses before slaughter. A total of 143 non-duplicate Salmonella were recovered from 1,000 fresh fecal swabs collected from four major pig slaughterhouses (49/600, 8.2％) and four major chicken slaughterhouses (94/400, 23.5％) between March and July 2016. Among Salmonella isolates from pigs, the predominant serovars were Salmonella Rissen (28/49, 57.1％) and Typhimurium (14/49, 28.6％), and high antimicrobial resistance rates were observed for tetracycline (44/49, 89.8％) and ampicillin (16/49, 32.7％). Class 1 integrons were detected in 10.2％ (5/49) of these isolates and all contained gene cassettes aadA2 (0.65 kb). Two β-lactamase genes were detected among these isolates, and most of these isolates carried blaTEM-1 (46/49), followed by blaOXA-1(4/49). Seven STs (MLST/ST, multilocus sequence typing) were detected in these isolates, and the predominant type was ST469 (19.6％). Among Salmonella isolates from chickens, the predominant serovars were Salmonella Indiana (67/94, 71.3％) and Enteritidis (23/94, 24.5％), and high antimicrobial resistance rates were observed for nalidixic acid (89/94, 94.7％), ampicillin (88/94, 93.6％) and tetracycline (81/94, 86.2％). Class 1 integrons were detected in 23 isolates (23/94, 24.5％), which contained empty integrons (0.15 kb, n=6) or gene cassettes drfA17-aadA5 (1.7 kb, n=6), aadA2 (1.2 kb, n=5), drfA16-blaPSE-1-aadA2-ereA2 (1.6 kb, n=5) or drfA1-aadA1 (1.4 kb, n=1). Three β-lactamase genes were detected, and all 94 isolates carried blaTEM-1, followed by blaCTX-M-55 (n=19) and blaSPE-1 (n=3). Five STs were found in these isolates, and the predominant type was ST17 (71.3％). Our findings indicated that Salmonella was widespread in animals at slaughter and may be transmitted from animal to fork.